TEACHER PERCEPTION TOWARDS THE USE OF CODE SWITCHING IN EFL CLASSROOM: A CASE STUDY IN ENGLISH INTENSIVE PROGRAM AT STATE ISLAMIC INSTITUTE IN CIREBON - Royani Afriani (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
The present study is descriptive qualitative research. The study aims to investigate and show the teachers perceptions toward the use of code-switching (CS) used by teachers in EFL classroom, especially in English intensive program at a State Islamic Institute. A four-section 20-item questionnaire was developed and distributed to the teachers. The data from the questionnaire were analyzed. The results display that teachers' perceptions are positive towards the use of code-switching in the EFL classroom. Teachers believe that the use of code-switching could help them in eliciting content, manage the classroom, and show interpersonal relations in the classroom. However, the use of code-switching is beneficial for learners but it also needs limitation because it could damage the process of language acquisition as learners don't get comprehensive input.